The US dollar: Safe haven - Despite rising US current account deficit - Martin Meurers; Berend Diekmann (Deutsche Bank Research, 2007)
The empirical analysis in this paper supports the view that the status of the US dollar as a “safe haven” is closely related to the development of the US current account and the US net foreign debt. Safe haven purchases of the US dollar can still be recorded in the 1989-2006 period despite the rapid growth of the US current account deficit since the mid-1990s. Possible explanations include the changed structure of US dollar investors, the concept of an implicit US-Asian currency peg and the increased prominence of alleviating valuation changes in the US net foreign position.
Keywords: 330; US-Dollar; USA; Zahlungsbilanzungleichgewicht; Leistungsbilanz; Reservewährung